AUDIT QUALITY IN INDONESIA’S PLANTATION SECTOR: THE NEXUS OF ESG AND FIRM CHARACHTERISTICS - Alfian Misran; Dinda Aulia Nazwa; Fira Nafwa Shafitri; Nur Athiyya Garneta (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2026)
This study examines the determinants of audit quality by integrating Environmental, Social, and Governance (ESG) performance and firm characteristics within a risk-based audit framework. It aims to assess whether ESG performance constitutes a meaningful risk signal in auditors decision-making relative to traditional financial and economic risk factors in a high-risk industry context. The empirical analysis focuses on plantation companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. Audit quality is proxied by audit fees and the likelihood of appointing Big Four auditors. ESG performance is measured using a composite ESG score constructed through content analysis of annual and sustainability reports. Panel data regression and logistic regression models are employed, incorporating robust standard errors as well as industry and year fixed effects to control for unobserved heterogeneity. The results show that firm size is positively and significantly associated with both audit fees and the probability of engaging Big Four auditors, while leverage exhibits a negative and significant relationship with both audit quality proxies. In contrast, ESG performance, operational complexity, and profitability do not demonstrate statistically significant effects on audit quality. This study introduces a hierarchical risk perspective by demonstrating that financially binding risk factors dominate audit outcomes, while ESG performance currently functions as a weak contextual signal in audit pricing and auditor selection decisions in a high ESG-exposure industry in an emerging market. The study is limited to a single industry focusing on firms operating in the plantation sector and covers a relatively short observation period from 2022 to 2024. Future research should examine additional industries, extend the observation window, and explore measures of ESG credibility, including third-party assurance.